Development of portable color detector: its application for determination of Munsell Soil Color - Heriyanto Syafutra; Muhammad Khoirul Anam; Faozan Ahmad; Desi Nadalia; Rudi Heryanto; Ganesha Antarnusa; Rofiqul Umam; Hirotaka Takahashi (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Soil color is a crucial indicator in soil science and agriculture; it provides information about soil properties and conditions. Typically, surveyors determine soil color by visually comparing the soil samples to the Munsell Soil Color Chart (MSCC). However, the accuracy of this method can be influenced by lighting conditions and the observer's subjectivity, leading to potential inconsistencies. This study introduces a portable color sensor device designed to improve the accuracy and consistency in determining the soil color and its MSCC notation compared to traditional visual methods. The device integrates a TCS3200 color sensor with a microcontroller to automate the color determination process. The device was validated by operating it to determine the color of 12 test paper sheets and four test soil types. The device can determine the color of the tested paper and soil well (100% accuracy); the result is displayed on the Liquid Crystal Display. It consistently achieved 100% accuracy for all measurements with varying ambient light intensity. The device is designed to be portable and easy to use, thus supporting field use for surveyors. Therefore, this device offers significant advantages in soil classification, fertility assessment, and environmental monitoring.